Markets, games, and strategic behavior An introduction to experimental economics - HOLT Charles A (Princeton Princeton University Press, 2019)
Economics is rapidly becoming a more experimental science, and the best way to convey insights from this research is to engage students in classroom simulations that motivate subsequent discussions and reading. In this expanded and updated second edition of Markets, Games, and Strategic Behavior, Charles Holt, one of the leaders in experimental economics, provides an unparalleled introduction to the study of economic behavior, organized around risky decisions, games of strategy, and economic markets that can be simulated in class.